In vitro Production of Atropine from Datura metel - Nithya M.; Sumaya Fathima S.; Sankar R.; Ajay A.; Vaibhav Kondiba Karape; Sedhupathi S. (BIO Web of Conferences)
The study involved the comprehensive analysis of Datura metel, focusing on the extraction and characterization of phytochemical compounds from both the crude plant material and callus extracts. After identification, leaves, internodes, and fruits underwent thorough cleaning and drying before being finely ground into powder. Extraction involved a precise process of mixing the powder with sterile water, gentle heating, filtration, and centrifugation, yielding a clear supernatant for further analysis. Phytochemical screening revealed the presence of various compounds like tannins, alkaloids, saponins, and flavonoids, with variations observed among plant parts and extracts. The rich phytochemical profile of Datura metel, suggesting its potential medicinal applications. Tests on crude plant and callus extracts provided insights into their chemical compositions. The callus extracts exhibited higher atropine content than normal plant extracts, hinting at the potential for in vitro culture to enhance atropine production. Variations in atropine content across different plant parts, providing valuable insights for pharmaceutical research and medicinal applications. This research highlights on the diverse phytochemical composition of Datura metel, warranting further exploration of its medicinal properties and cultivation techniques. The amount of atropine in each source varies: 1.25 mg/g of atropine is found in stem calli, 1.09 mg/g is found in leaf calli, 1.53 mg/g is found in fruit calli, and 1.12 mg/g is found in flower calli. that the amounts of atropine vary according to the tissue from which the calli originate, with the highest concentration found in calli produced from fruit, followed by calli originating from stems, flowers, and leaves. These studies urge for more study into the therapeutic effects of Datura metel and advance our awareness of its potential in pharmaceutical applications.